2019
DOI: 10.3389/fpsyg.2019.02435
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Academic, Personality, and Emotion-Related Predictors of University Academic Performance

Abstract: This paper investigates the relationships between personality (i.e., trait Emotional Intelligence – trait EI – and the Big Five) and academic performance (AP). Academic motivation, procrastination, and major satisfaction were also studied. The sample consisted of 201 Lebanese undergraduates. The model represented a good fit. There was a negative direct effect of procrastination on AP and positive direct effects of major satisfaction and absorption on AP. Trait EI showed a negative direct effect on procrastinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The regulatory BF components (C, E) proved to be protective factors against stress (its factors and symptoms), while the non-regulatory factors (O, A) were unrelated to stress factors and symptoms, and the dysregulatory factor (N) appeared as a risk factor for stress (factors and symptoms). These results concur with prior evidence ( 124 , 125 ). Different studies have found that the C and E personality traits are predictors of academic resilience.…”
Section: Discussionsupporting
confidence: 93%
“…The regulatory BF components (C, E) proved to be protective factors against stress (its factors and symptoms), while the non-regulatory factors (O, A) were unrelated to stress factors and symptoms, and the dysregulatory factor (N) appeared as a risk factor for stress (factors and symptoms). These results concur with prior evidence ( 124 , 125 ). Different studies have found that the C and E personality traits are predictors of academic resilience.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Watson and Watson [27] examined how much EI and coping skills predicted academic stress in first-year university students, and they found that the absence of emotional intelligence was a good predictor of stress. Similarly, recent studies show a negative relationship between EI and academic stress [1,28,29].…”
Section: Academic Stress In the University Contextmentioning
confidence: 74%
“…Procrastination and anxiety are well-known detrimental variables to academic achievement in online learning, with the former two affecting the latter ( Cormack, Eagle, & Davies, 2020 ; Frazier, Gabriel, Merians, & Lust, 2019 ; Kim & Nembhard, 2019 ; Pascoe, Hetrick, & Parker, 2020 ; Sanchez-Ruiz & El Khoury, 2019 ). The outbreak of the COVID-19 pandemic may surely have amplified their relevance in the academic achievement of students, but in a more nuanced way than it might seem wherever lockdown has been enforced.…”
Section: Discussionmentioning
confidence: 99%